PENGARUH MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) BERBASIS DIFERENSIASI TERHADAP HASIL BELAJAR SISWA KELAS V PADA KONSEP PEMBAGIAN BILANGAN DESIMAL DI UPT SDN 067241 MEDAN - Reflina Sinaga; Afrida Khairani Rangkuti; Amanda Fadhilah Ramadhani; Chairunisa Tampu Bolon; Indah Ocktavia; Nadila Fitria; Riswanda Hugo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to improve student learning outcomes by using the Differentiation-Based Team Games Tournament (TGT) learning model in Mathematics in the Concept of Decimal Number Division. The subjects in this study were 26 fifth grade students, 13 of whom were male and 13 female. The technique used by the researcher included the stages of planning, action, observation, and reflection. In cycle I, it can be seen that the results of the student learning test are still far from the expected target, which is 58% of the number of students. A class can be considered to have completed its learning if at least 80% of students have achieved completeness. Furthermore, observation data on student learning outcomes in cycle II showed an increase in learning outcomes from the previous cycle, so that learning can be said to be successful where 88% of student learning completeness was achieved and had achieved classical completeness. So this study shows an increase in student learning outcomes in Mathematics in the Concept of Decimal Number Division in class V UPT SDN 067241 Medan in the 2024/2025 Academic Year.